Modeling of structure and functions of Antarctic ecosystems with the help of GIS-technologies - Tashyrev, O.B.; Kobzar, L.I.; Usenko, V.P.; Morgun, S.I.; Seredynin, E.S. (Український антарктичний журнал, 2010)
The article presents main approaches to ecosystem modeling with using of GIStechnologies. It was shown that geoinformation systems allow to store, systematize on the spatial principle and analyze information related to biotic and abiotic parameters of ecosystems. Methods of long-termed monitoring of ecosystem structure and functioning, earth surface relief modeling, developing models of ecosystems of lower hierarchical levels were described. Ways of further development of methods for collecting and analyzing data were contemplated. Models of the microorganisms resistance to toxic metals on the biogeographical polygon on island Galindez and models of pigmented forms distribution and a ratio of quantity of pigmented to non-pigmented forms of microorganisms in rock biocoenoses were created. Wide distribution of metal-resistant microorganisms on the biogeographical polygon, their presence in mosses, lichens, sludge, soil and presence of pigmented forms bacteria, micromycetes, yeasts in biocenoses of vertical cliffs were shown. It was shown that usage of GIS-technologies allows to identify the areas, which are the most perspective for searching of producers of biologically active substances.